The Influence of Knowledge, Skills, and Attitudes on Midwife Performance in Documenting MCH Books - Dewi Anggraini; Budi Astyandini; Emi Kusumawardani; Andrafikar; Widya Nengsih (CV. Get Press Indonesia, 2025)
Maternal and Child Health Book (MCH Book) documentation is an important part of midwifery services that contributes to the monitoring of maternal and child health. This study aimed to analyze the relationship between knowledge, skills, attitudes, and the performance of midwives in MCH Book documentation. A quantitative method was used with an observational analytic approach and a cross-sectional design. Data were collected through observations and questionnaires administered to midwives in health facilities. The data were analyzed using the chi-square statistical test to determine the relationship between midwives’ knowledge, skills, and attitudes with their performance in MCH Book documentation. Statistical test results showed that knowledge and skills did not have a significant relationship with documentation performance (knowledge: p-value = 0.067 > α = 0.05; skills: p-value = 0.054 > α = 0.05). However, attitudes had a significant relationship with performance (p-value = 0.005 < α = 0.05). These findings indicate that improving skills or knowledge alone is not sufficient to enhance documentation quality; a positive attitude toward the importance of documentation plays a more crucial role. Therefore, training and coaching programs should focus not only on improving technical abilities but also on fostering professional attitudes and awareness regarding the importance of accurate and complete obstetric documentation. Strengthening these aspects is essential to improving the quality of maternal and child health records in healthcare settings.